Attitudes of Distance Learning Students at UKM’s Faculty of Islamic Studies Towards Learning Arabic Language Skill Courses - Zulazhan, Ab. Halim; Zamri, Arifin; Ezad Azraai, amsari (2014)
Attitude is the most important element in determining one’s achievements in learning the Arabic language either as a full or part-time student. This study is based on the Gardner's socio-educational model, and focuses on two types of motivational orientation, which are integrative and instrumental, and attitudes toward the learning conditions. The main purpose of this study is to identify the level of integrative orientation, attitudes toward the learning conditions and instrumental orientation among students in a Distance Learning (DL) program at the Faculty of Islamic Studies (FPI), Universiti Kebangsaan Malaysia (UKM, The National University of Malaysia). This study used a quantitative research design. Data were collected through questionnaires and analyzed descriptively. A total of 170 distance learning students were selected using the simple random sampling technique. Findings show that the students possessed a high level of integrative orientation and their attitudes toward learning environment were positive. The level of instrumental orientation, on the other hand, was very high with the instrumental orientation obtaining the highest mean score. One of the implications that can be drawn from this study is that teachers and students need to take into account and emphasize integrative orientation, attitudes toward learning conditions and instrumental orientation in order to develop a positive attitude in students who aim to master the Arabic language. Other than that, educational institutions should provide support and carry out other related activities and programs in order to ensure that students consistently have positive attitudes whilst achieving excellent results in learning the Arabic language.